Self-Discrepancy pada Pengguna Roleplayer: Bagaimana Peranan Penerimaan Diri? - Putri, Adelia Elsiana; Pratikto, Herlan; Suhadianto, Suhadianto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract This research aims to determine whether there is a relationship between self-acceptance and self-discrepancy among roleplayer users. The research participants amounted to 170 individuals obtained through purposive sampling. This study utilizes two scales: the self-acceptance scale and the self-discrepancy scale. The data collection instrument in this research employs the Likert scale model. The sampling technique used in this study is correlational. Data analysis in this research employs the Pearson product-moment correlation method. Based on the data analysis results obtained from the SPSS version 16.0 (Statistical Product and Service Solution) for Windows, there is a significant negative correlation. This means that the higher the level of self-acceptance possessed by an individual, the lower the likelihood of that individual experiencing self-discrepancy. Conversely, if an individual has a lower level of self-acceptance, there is a higher likelihood of experiencing self-discrepancy. Abstrak Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara penerimaan diri dengan self-discrepancy pada pengguna roleplayer. Partisipan penelitian berjumlah 170 orang yang diperoleh melalui teknik purposive sampling. Penelitian ini menggunakan dua skala yaitu skala penerimaan diri dan skala self-discrepancy. Instrumen pengambilan data pada penelitian ini menggunakan model skala likert. Teknik sampel yang digunakan pada penelitian ini menggunakan teknik korelasional. Analisis data pada penelitian ini menggunakan metode korelasi pearson product moment. Berdasarkan hasil analisis data yang diperoleh dari program computer SPSS versi 16.0 (Statistical Product and Service Solution) for Windows terdapat hasil analisis data yang menunjukkan bahwa terdapat hubungan negatif yang sigifikan. Artinya semakin tinggi tingkat penerimaan diri yang dimiliki oleh individu maka akan semakin rendah individu tersebut akan mengalami self-discrepancy. Sebaliknya, apabila semakin rendah tingkat penerimaan diri yang dimiliki oleh individu maka akan semakin tinggi individu tersebut akan mengalami self-discrepancy.